V VALIDITY OF GEOPARK INTEGRATED NATURAL SCIENCE LEARNING RESOURCES TO ENRICH STUDENTS' LOCAL WISDOM IN ELEMENTARY SCHOOL - Budiastra, A.A. Ketut; Susy Puspitasari; Nia Erlina; Memet Casmat; Kadarisman (Advances in Social Sciences Research Journal, 2022)
Quality education is needed to form quality human resources. Learning resources are one of the supporting factors for a quality learning process. In general, this study aims to examine the validity of geopark integrated science video learning resources to enrich students' local wisdom in elementary schools. The subjects of this study amounted to three validators. The design of this research is research and development. Validity testing is done by using the Product Moment Correlation formula. Testing the instrument's reliability was carried out using the Cronbach Alpha formula because the data was in the form of interval data. This study shows that the learning resources in videos meet the validity of the content and constructs. Pearson Correlation (r) on each validator shows > rt = .432 with valid criteria. Cronbach's Alpha value on content > .60, then the decision making in the reliability test on content by 3 validators was concluded to be reliable. Learning resources in the form of videos meet the reliability requirements based on the assessment of three validators. The validator's recommendations on learning resources in the form of videos strengthen the content of learning resources. This research has a contribution as a geopark integrated science learning resource for elementary school students.